Quantitative assessment and genomic profiling of Campylobacter dynamics in poultry processing: a case study in the United Arab Emirates integrated abattoir system - Habib, Ihab; Mohamed, Mohamed-Yousif Ibrahim; Lakshmi, Glindya Bhagya; Al Marzooqi, Hassan Mohamed; Afifi, Hanan Sobhy; Shehata, Mohamed Gamal; Khan, Mushtaq; Ghazawi, Akela; Abdalla, Afra; Anes, Febin (Frontiers in Microbiology, 2024)
In the United Arab Emirates, no previous research has investigated the dynamics of the foodborne pathogen Campylobacter in broiler abattoir processing. This study conducted in one of the largest poultry producers in the UAE, following each key slaughter stage-defeathering, evisceration, and final chilling-five broiler carcasses were collected from ten slaughter batches over a year. Additionally, one caecum was obtained from 15 chickens in each slaughter batch to evaluate the flock colonization. In total, 300 samples (150 carcasses and 150 caeca) were collected and enumerated for Campylobacter using standard methods. Campylobacter was pervasive in caecal samples from all slaughter batches, with 86% of carcasses post-defeathering and evisceration stages and 94% postchilling tested positive for Campylobacter. Campylobacter coli predominates in 55.2% of positive samples, followed by Campylobacter jejuni in 21%, with both species co-existing in 23.8% of the samples. Campylobacter counts in caecal contents ranged from 6.7 to 8.5 log10 CFU/g, decreasing postdefeathering and evisceration to 3.5 log10 CFU/g of neck skin and further to 3.2 log10 CFU/g of neck skin post-evisceration. After chilling, 70% of carcasses exceeded 3 log10 CFU/g of neck skin. Wholegenome sequencing (WGS) of 48 isolates unveiled diverse sequence types and clusters, with isolates sharing the same clusters (less than 20 single nucleotide polymorphisms) between different farms, different flocks within the same farm, as well as in consecutive slaughter batches, indicating crosscontamination. Multiple antimicrobial resistance genes and mutations in gyrA T86I (conferring fluoroquinolone resistance) and an RNA mutation (23S r.2075; conferring macrolide resistance) were widespread, with variations between C. coli and C. jejuni. WGS results revealed that selected virulence genes (pglG, pseD, pseI, flaA, flaB, cdtA, and cdtC) were significantly present in C. jejuni compared to C. coli isolates. This study offers the first insights into Campylobacter dynamics in poultry processing in the UAE. This work provides a base for future research to explore additional contributors to Campylobacter contamination in primary production. In conclusion, effective Campylobacter management demands a comprehensive approach addressing potential contamination sources at every production and processing stage, guided by continued microbiological surveillance and genomic analysis to safeguard public health and food safety.